Enhancing epi-cedrol production in escherichia coli by fusion expression of farnesyl pyrophosphate synthase and epi-cedrol synthase - Navale, Govinda R; Sharma, Poojadevi; Said, Madhukar S; Ramkumar, Sudha; Dharne, Mahesh S; Thulasiram, H., V; Shinde, Sandip S (Engineering in Life Science, 2019)
Terpene synthase catalyses acyclic diphosphate farnesyl diphosphate into desired sesquiterpenes. In this study, a fusion enzyme was constructed by linking Santalum album farnesyl pyrophosphate synthase (SaFPPS) individually with terpene synthase and Artemisia annua Epi-cedrol synthase (AaECS). The stop codon at the N-terminus of SaFPPS was removed and replaced by a short peptide (GSGGS) to introduce a linker between the two open reading frames. This fusion clone was expressed in Escherichia coli Rosseta DE3 cells. The fusion enzyme FPPS-ECS produced sesquiterpene 8-epi-cedrol from substrates isopentenyl pyrophosphate and dimethylallyl pyrophosphate through sequential reactions. The K-m values for FPPS-ECS for isopentyl diphosphate was 4.71 mu M. The fusion enzyme carried out the efficient conversion of IPP to epi-cedrol, in comparison to single enzymes SaFPPS and AaECS when combined together in enzyme assay over time. Further, the recombinant E. coli BL21 strain harbouring fusion plasmid successfully produced epi-cedrol in fermentation medium. The strain having fusion plasmid (pET32a-FPPS-ECS) produced 1.084 +/- 0.09 mg/L epi-cedrol, while the strain harbouring mixed plasmid (pRSETB-FPPS and pET28a-ECS) showed 1.002 +/- 0.07 mg/L titre in fermentation medium by overexpression and MEP pathway utilization. Structural analysis was done by I-TASSER server and docking was done by AutoDock Vina software, which suggested that secondary structure of the N- C terminal domain and their relative positions to functional domains of the fusion enzyme was greatly significant to the catalytic properties of the fusion enzymatic complex than individual enzymes.

Targeted metabolite profiling and de novo transcriptome sequencing reveal the key terpene synthase genes in medicinally important plant, Couroupita guianensis Aubl - Thulasiram, Hirekodathakallu V.; Karegaonkar, Shrikant Jagannathrao; Sharma, Poojadevi; Kumar, Ashish; Ramkumar, Sudha; Pandreka, Avinash (Plant Genetic Resources-Characterization and Utilization, 2023)
The Lecythidaceae family tree, Couroupita guianensis Aubl, popularly known as Nagpushpa, is a widely cultivated ornamental tree with several uses in traditional medicine. The tree is revered as highly sacred in Indian traditional culture due to its uniquely shaped, fragrant flowers. Considering the significance, we were prompted to carry out the metabolite and transcriptome analysis of Nagapushpa. The flower, petals, stamen, stem and leaf of C. guianensis were metabolically profiled, and it was discovered that the flower tissue contained the highest terpenoid reservoir. A number of terpenoid pathway transcripts were also found in the flower tissue after transcriptome profiling. KEGG pathway mapping was carried out to correlate transcript sequences with the biosynthesis of different types of terpenes. We were able to clone three full-length terpene synthase gene candidates, i.e. monoterpene ocimene synthase, diterpene ent-kaurene synthase and sesquiterpene farnesene synthase. The transcript expression of selected terpene synthase genes was also verified in flower tissue. These cloned sequences were used for in silico structural investigations and protein function prediction at the level of 3D structure. The data presented in this study provide a comprehensive resource for the metabolic and transcriptomic profiles of C. guianensis. The study paves the way towards the elucidation of terpene biosynthetic pathway in C. guianensis and heterologous production of useful terpenoids in the future.
Keywords: Couroupita guianensis Aubl; flower; Metabolite profiling; terpene synthases; Transcriptomics